Data and computer communications - Stallings, William (Prentice Hall, 2000)
The sixth edition of Data and Computer Communications features improved illustrations, new coverage of Gigabit Ethernet, a survey of ADSL, new coverage of IP multicasting and reports on the very latest technologies in hardware and software.